Emergency Department Visits for Influenza A(H1N1)pdm09, Davidson County, Tennessee, USA - Wesley H. Self; Carlos G. Grijalva; Yuwei Zhu; H. Keipp Talbot; Astride Jules; Kyle E. Widmer; Kathryn M. Edwards; John V. Williams; David K. Shay; Marie R. Griffin (Emerging Infectious Diseases, 2012)
To determine the number of emergency department visits attributable to influenza A(H1N1)pdm09 in Davidson County, Tennessee, USA, we used active, population-based surveillance and laboratory-confirmed influenza data. We estimated ≈10 visits per 1,000 residents during the pandemic period. This estimate should help emergency departments prepare for future pandemics.